2022
DOI: 10.1097/inf.0000000000003689
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Health Disparities Associated With Multisystem Inflammatory Syndrome in Children After SARS-CoV-2 Infection

Abstract: Background: Multisystem inflammatory syndrome in children (MIS-C) is a postinfectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–related complication that has disproportionately affected racial/ethnic minority children. We conducted a pilot study to investigate risk factors for MIS-C aiming to understand MIS-C disparities. Methods: This case-control study included MIS-C cases and SARS-CoV-2-positive outpatient controls less than 18 years old frequency-matched 4:1 to cases by age group and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…On average, symptoms of MIS-C first present two to four weeks after acute COVID-19 illness and can involve a constellation of respiratory, gastrointestinal, cardiac, renal, dermatologic, and neurological symptoms that in 60% of cases result in hospitalization and possible ICU stay with invasive mechanical ventilation required due to inadequate oxygenation 2 . Diagnosis of MIS-C is challenging due to overlapping clinical features with other hyperinflammatory illnesses, such as Kawasaki Disease (KD) and Toxic Shock Syndrome (TSS) 3,4 , and the lack of objective biomarker based diagnostic tests hinders accurate diagnosis and effective management and treatment for this condition 5 . As of August 2022, the CDC has reported 8,798 cases of MIS-C and 71 deaths attributed to MIS-C in children 6 , defined as individuals under 21 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…On average, symptoms of MIS-C first present two to four weeks after acute COVID-19 illness and can involve a constellation of respiratory, gastrointestinal, cardiac, renal, dermatologic, and neurological symptoms that in 60% of cases result in hospitalization and possible ICU stay with invasive mechanical ventilation required due to inadequate oxygenation 2 . Diagnosis of MIS-C is challenging due to overlapping clinical features with other hyperinflammatory illnesses, such as Kawasaki Disease (KD) and Toxic Shock Syndrome (TSS) 3,4 , and the lack of objective biomarker based diagnostic tests hinders accurate diagnosis and effective management and treatment for this condition 5 . As of August 2022, the CDC has reported 8,798 cases of MIS-C and 71 deaths attributed to MIS-C in children 6 , defined as individuals under 21 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the methodology, characteristics of findings, presence of racial disparity, quality appraisal, and country of study is presented in Table 3 . All of the reviewed studies employed a quantitative methodology [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and used surveillance data collected from electronic health record systems. The studies were conducted from January 2016 to December 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies (95%) identified the presence of racial disparities in the occurrence rate of common infectious respiratory diseases, such as SARS-CoV-2 (COVID-19), SARS-CoV-2 (COVID-19)-related illnesses, influenza virus, respiratory syncytial virus (RSV), human metapneumovirus (HMPV), human parainfluenza viruses (HPIVs), streptococcus, staphylococcus aureus, and rhinovirus [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], among children in the United States. One study conducted by Perez et al [ 13 ] identified the presence of racial disparities in the occurrence rate of infectious respiratory diseases, such as influenza, respiratory syncytial virus (RSV), human metapneumovirus (HMPV), human parainfluenza viruses (HPIVs), and SARS-CoV-2 (COVID-19), with Blacks or African Americans and Hispanics/Latinos carrying the majority (59%) of the burden of infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations